Water Quality of Rivers and Ponds on DKI Jakarta - Hendrawan, Diana (Makara Journal of Technology, 2005)
Water Quality of Rivers and Ponds on DKI Jakarta. Thirteen big rivers, some small rivers, and 40 ponds spread over districts at Jakarta city are potential to support human being life. As the population is growing and the usage of stream water is increasing, the condition and quality of rivers and ponds are changing. Crowd housing can affect rivers and ponds pollution, as the people awareness about clean and healthy environment is less. Stream water pollution assessment can be done by counting the effect of pollutant to life of stream water organisms. This assessment unit could be classified into physics, chemical, and biological parameter. To know the water quality, those parameters are transformed into one single value, that is Water Quality Index. The calculation result of Water Quality Index value shows that 83 % of rivers and 79 % of ponds are bad. This condition is caused by less people and government awareness to maintain rivers and ponds.